Isolasi dan Uji Toksisitas Fraksi Etil Asetat Spons Ancorina sp. Asal Zona Intertidal Pantai Wediombo Gunung Kidul Yogyakarta - Yuni Nurfiana (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2017)
Sponges are one of the marine organisms that contain various bioactive compounds. The purpose of this study was to isolate and test the toxicity of the ethyl acetate fraction of Ancorina sp. from the intertidal zone of Wediombo Beach, Gunungkidul. Isolation was carried out by maceration method with methanol:dichloromethane 1:1 (v/v) solvent. The dichloromethane extract was evaporated and partitioned with ethyl acetate:water (1:2). The ethyl acetate extract was separated and evaporated to obtain a thick extract which was then fractionated using column chromatography. The toxicity test was carried out using the Brine Shrimp Lethality Test (BSLT) method. The isolation produced 7 ethyl acetate fractions, respectively, with masses: 71.1; 86.4; 69.3; 88.8; 78.7; 97.5; and 100.2 mg. The results of the toxicity test for the seven fractions showed a range of toxic and very toxic LC50 values.